Aspectualidade da microconstrução [IRauxVp] na fala goiana - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The basic sentential patterns of the language are organized around the verb. These patterns can be formed by full verbs or periphrases, including the microconstruction [IRauxVp], which, in its prototypical form, consists of the auxiliary verb ir and a verbal form in the infinitive, gerund or participle. This work presents the results of a study of this microconstruction in Goiás speech, considering the aspectual notions that this constructional pattern encodes. To describe the object, we took as a basis the discussions undertaken, mainly, by Construction Grammar and Cognitive Linguistics. Thus, based on authors such as: Bybee (2016), Croft (2001), Ferrari (2018), Fillmore (1982), Goldberg (1995, 2006), Langacker (1987, 2008), Lakoff and Johnson (1980) , Lakoff (1987, 1990), Traugott and Trousdale (2013), Taylor (1995) among others. To verify what the aspectual specificities of the microconstruction [IRauxVp]] would be, we used speech data from the contemporary Portuguese Project spoken in Goiás — Fala Goiana. We sought, at first, to identify the constructs organized based on the auxiliary verb ir and, then, we sought to verify the formal and functional aspects of the microconstruction. Subsequently, we check which nominal form of the main verb is most productive and which aspectual types the microconstruction [IRauxVp] encodes. Finally, we check the expression of the aspect in the main verb and analyze the aspect by verb tenses. The results showed that there are other clause elements inserted in the constructional pattern of our object of analysis. There is also a preference for using microconstruction with the main verb in the infinitive and verb tense in the future. We also identified a predominance of the active voice, to the detriment of the passive voice. The auxiliary verb shares grammatical properties with the main verb and the microconstruction [IRauxVp] does not update all aspectuality marks in Goiás speech. Based on the results, we consider that the microconstruction [IRauxVp] is not a prototypical aspect marker and that the nominal form of the main verb, temporal inflections and adverbial constructions influence aspectual coding.
Aspectuality of microconstruction [IRauxVp] in Goiás speech
Keywords: Língua; Predicação; Microconstrução [IRauxVp]; Aspecto; Language; Predication; Microconstruction [IRauxVp]; Aspect; LINGUISTICA::TEORIA E ANALISE LINGUISTICA